\(\Rightarrow4C=4^2+4^3+...+4^{n+1}\)
\(\Rightarrow4C-C=\left(4^2+4^3+...+4^{n+1}\right)-\left(4+4^2+...+4^n\right)\)
\(\Rightarrow3C=4^{n+1}-4\)
\(\Rightarrow C=\frac{4^{n+1}-4}{3}\)
\(4C=4^2+4^3+4^4+...+4^{n+1}\)
\(4C-C=4^2+4^3+...+4^{n+1}-4-4^2-...-4^n\)
\(3C=4^{n+1}-4\)
\(C=\frac{4^{n+1}-4}{3}\)
\(C=4+4^2+4^3+....+4^n\)
\(4C=4^2+4^3+4^4+.....+4^{n+1}\)
\(3C=4^{n+1}-4\)
\(C=\frac{4^{n+1}-4}{3}\)
ta có \(c=4+4^2+4^3+...+4^n\)
\(\Rightarrow4c=4^2+4^3+4^4+...+4^{n+1}\)
\(\Rightarrow4c-c=3c=4^{n+1}-4\)
\(\Rightarrow c=\frac{4^{n+1}-4}{3}\)